The Mammals of Pakistan - Roberts, T. J.; Foreword by His Royal Highness Prince Bernhard of the Netherlands (Karachi Oxford University Press, 1997)
This text documents all the known existing mammalian fauna of Pakistan. Originally published in 1977, it has been brought up to date with new information. The 167 species accounts are supported by distribution maps, over 90 black and white drawings, and 24 colour plates.
Include Index, Notes, Appendix, Glossary and colored Illustrations.
Keywords: Mammals -- Mammals -- Pakistan